Systemic ß adrenergic stimulation/ sympathetic nerve system stimulation influences intraocular RAS through cAMP in the RPE. (December 2019) - Martins, Joana Raquel; Reichhart, Nadine; Kociok, Nobert; Stindl, Julia; Foeckler, Renate; Lachmann, Peter; Todorov, Vladimir; Castrop, Hayo; Strauß, Olaf
Abstract: Several lines of evidence support the existence of a renin-angiotensin system (RAS) in the retina that is separated from the blood stream by the retinal pigment epithelium (RPE). Under physiological conditions, increased activity of intraretinal RAS regulates neuronal activity of the retina but patho-physiologically participates in retinal degeneration such as hypertensive or diabetic retinopathy. Interestingly, the RPE appears to be a modulator of intraretinal RAS in response to changes in systemic RAS. As increased systemic RAS activity is associated with increased sympathetic tonus, we investigated whether systemic β-adrenergic stimulation of the RPE also modulates renin expression in the RPE. In vivo, the mouse RPE expresses the β-adrenergic receptor subtypes 1 and 2. Staining of retina sagittal sections showed tyrosine hydroxylase positive nerve endings in the choroid indicating adrenaline/noradrenaline production sites in close proximity to the RPE. Systemic infusion of isoproterenol increased renin expression in the RPE but not in the retina. This increase was sensitive to concomitant systemic application of the angiotensin-2 receptor-type-1 blocker losartan. In vitro analysis of renin gene expression using polarized porcine RPE showed that the activity of the renin promoter can be increased by cAMP stimulation (IBMX/forskolin) but was not influenced by angiotensin-2. Thus, with the identification of the β-adrenergic system we added a new regulator of the retinal RAS with relevance for retinal function and pathology. Furthermore, it appears that the RPE is not only a close interaction partner of the photoreceptors but also a regulator or retinal activity in general. Highlights: The retinal pigment epithelium (RPE) forms an interface between the body system and retina. Basolateral plasma membrane receptors make the RPE being an active interface between the body system and the retina. We show that β-adrenergic stimulation increases the renin production by the RPE and thus retinal renin-angiotensin system. Close sympathetic nerves in the choroid suggest that sympathetic activity influences retinal function and retinal pathology.